STUDY OF TRAFFIC ACCIDENTS BASED ON CASE MATERIALS - Siddikov Kutbiddin Marufjonovich (Лучшие интеллектуальные исследования, 2024)
Abstract: It is planned to study the state of traffic accidents registered in 2023 at the Andijan branch of the Republican Scientific and Practical Center for Forensic Medical Examination.